Transcervical Foley catheter– endovenous oxytocin or oxytocin alone for induction of labor in term pregnancies - Fuenmayor-Beltrán, Mariedg (2017)
Objective: To compare the effectiveness of transcervical Foley catheter – oxytocin with oxytocin alone for labor induction in term pregnancies. Design: Case-control study. Setting: Hospital Central “Dr. Urquinaona”, Maracaibo, Venezuela. Participants: Pregnant women undergoing cervical ripening and labor induction were randomly assigned to be treated with transcervical Foley catheter – oxytocin (group A) or oxytocin alone (group B). Main outcome measures: General characteristics, interval between beginning of induction and delivery, vaginal birth rate, maternal complications, perinatal variables, and adverse effects were evaluated. Results: There were no significant differences between groups in general characteristics (p = ns). Patients of group A showed a shorter interval between the beginning of induction and delivery compared with patients in group B (p < 0.05). There was no significant difference in vaginal birth rate between groups (p = ns). Newborns of both groups had similar mean values of Apgar scores at 1 minute and 5 minutes (p = ns). The most common adverse effect in both groups was nausea, but there were no significant differences between groups in frequency of adverse effects (p = ns). Conclusions: Use of transcervical Foley catheter – oxytocin shortened the interval between beginning of induction and delivery compared with oxytocin alone, with similar incidence of maternal and perinatal adverse effects.